Challenges and opportunities for the development of the NAMAs in the livestock sector in Colombia and Costa Rica - Serna-Hurtado, Laura Patricia; Escobar, Daniel; Tapasco, Jeimar; Arango, Jacobo; Chirinda, Ngonidzashe; Chacón, Mauricio; Segura, Jorge; Villanueva, Cristóbal (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
Livestock NAMAs seek to transform livestock production in Colombia and Costa Rica.